2010
DOI: 10.1007/s10734-010-9356-0
|View full text |Cite
|
Sign up to set email alerts
|

University studies as a side job: causes and consequences of massive student employment in Estonia

Abstract: Student employment is increasingly common in many countries. Compared to earlier decades, not only more students work but they also work longer hours. Among European countries Estonia is one of the clear ''leaders'' in student employment. This study uses survey data from 2,496 students in Estonian public and private universities to examine the reasons for working on such a massive scale and its consequences on academic success. The results show that, unlike in most other countries, Estonian students from more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 16 publications
(16 reference statements)
7
69
0
10
Order By: Relevance
“…Beerkens et al (2010) find only a very small negative effect on academic performance and labour market outcomes for students in Estonia. Employment parallel to study sends a signal to employers about the quality of the graduates who enter the labour market.…”
Section: How Working Impacts the Labour Market Outcomes For Studentsmentioning
confidence: 64%
“…Beerkens et al (2010) find only a very small negative effect on academic performance and labour market outcomes for students in Estonia. Employment parallel to study sends a signal to employers about the quality of the graduates who enter the labour market.…”
Section: How Working Impacts the Labour Market Outcomes For Studentsmentioning
confidence: 64%
“…Structural changes are also visible on the job market, where a greater deal of combining work and education opportunities occurred due to the development of nonstandard types of employment suitable for students, such as part-time work, flexible working hours employment, remote work, and outsourcing or freelancing possibilities [3,8].…”
Section: Theoretical Framework: Incidence and Impact Of Term-time Empmentioning
confidence: 99%
“…Over the past two decades a rapid expansion of higher education student numbers has been evident [1], and given this so called "massification" of higher education, employment during studies has become a common phenomenon worldwide [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In Estonia, it is common that young people want to work while studying -a survey carried out in Estonia showed that 61% of students work during their studies [35]. As for IT students, earning extra money (42%) and getting practice in the field (28%) are the main reasons for working [30].…”
Section: International Journal Of Information and Education Technologmentioning
confidence: 99%